Strategic Leadership for Industry 4.0 Adaptation in Vocational Education: A Qualitative Case Study of Sensemaking and Resource Orchestration in Indonesia - Tentri Septiyani; Mukhsin Mukhsin; Nurainiyah Nurainiyah (Program Studi Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2026)
Strategic leadership has become central to preparing vocational education for the Fourth Industrial Revolution (Industry 4.0). However, existing strategic leadership scholarship is predominantly grounded in resource-rich, Western educational systems, offering limited explanations of how vocational school leaders sustain organizational adaptation amid institutional and material constraints in the Global South. This study addresses this gap by examining how strategic leadership is enacted in a public vocational school in Bandung, Indonesia. Employing an instrumental qualitative case study, data were generated through semi-structured interviews, non-participant observations, and document analysis, and analyzed using thematic analysis. The findings demonstrate that strategic adaptation is fundamentally a relational and context-sensitive leadership capability characterized by three interconnected practices: contextual sensemaking, negotiated organizational alignment, and entrepreneurial resource orchestration. Rather than relying on hierarchical decision-making, school leaders translated Industry 4.0 demands into locally meaningful actions through continuous dialogue with teachers and industry partners, transforming external pressures into collaborative organizational learning. A key contribution of the study is the identification of capital alchemy, a strategic mechanism that deliberately converts intangible assets—including institutional reputation, teacher expertise, student achievements, and social legitimacy—into tangible resources such as Corporate Social Responsibility (CSR) funding, industry partnerships, and infrastructure development. This concept extends strategic leadership theory by demonstrating how symbolic, social, and human capital can compensate for material resource scarcity and function as strategic assets for organizational transformation. The study proposes a contextually grounded model of relationship-based strategic leadership that broadens prevailing resource-centered perspectives and offers practical implications for leadership development, educational governance, and vocational education policy in resource-constrained settings across the Global South.